Cancer Cell Plasticity in Urothelial Carcinoma: When it Give Rise to Melanoma - Fontaine, Alix; Roblet, Denis; Benmeziani, Racha; Fromont, Gaelle (Archives of Clinical and Medical Case Reports, 2022)
Primary bladder melanoma is very rare, and the association with urothelial carcinoma has never been described to date. We report a case of a biphasic tumor of the bladder, composed of high grade urothelial carcinoma adjacent to melanoma, characterized using immunohistochemistry and DNA sequencing. The urothelial component was positive for pan-cytokeratin and GATA3, and negative for melanoma markers HMB45, Melan A, and Sox10. In contrast, the melanocytic component was negative for pancytokeratin and positive for HMB45, Melan A, and Sox10. Moreover, some nuclei were weakly stained for GATA3, a transcription factor of the urothelial lineage. Molecular genetic analysis showed that both components shared a never described identical serine/threonine kinase 11 (STK11) D365G molecular alteration, and a c.-124C>T Telomerase Reverse Transcriptase (TERT) promoter mutation, an early event in urothelial carcinogenesis. Our report underlines the phenotypic plasticity of urothelial carcinomas, and raises the question of an urothelial origin of urinary tract melanomas.